Should non-bacteraemic patients with a colonized catheter receive antimicrobial therapy?. (September 2017) - De Egea, V.; Guembe, M.; Rodríguez-Borlado, A.; Pérez-Granda, M.J.; Sánchez-Carrillo, C.; Bouza, E.
Highlights: The outcomes of patients with colonized catheters and no bacteraemia were assessed. The impact of antimicrobial therapy on the outcomes of these patients were evaluated. No association was found between the use of targeted antimicrobial therapy and a poor outcome. Abstract: Objectives: The impact of antimicrobial therapy on the outcomes of patients with colonized catheters and no bacteraemia has not been assessed. This study assessed whether targeted antibiotic therapy is related to a poor outcome in patients with positive cultures of blood drawn through a non-tunnelled central venous catheter (CVC) and without concomitant bacteraemia. Methods: This was a retrospective study involving adult patients with positive blood cultures drawn through a CVC and negative peripheral vein blood cultures. Patients were classified into two groups: those with clinical improvement and those with a poor outcome. These two groups were compared. The outcome was considered poor in the presence of one or more of the following: death, bacteraemia or other infection due to the same microorganism, and evidence of catheter-related bloodstream infection. Results: A total of 100 patients were included (31 with a poor outcome). The only independent predictors of a poor outcome were a McCabe and Jackson score of 1–2 and a median APACHE score of 5. No association was found between the use of targeted antimicrobial therapy and a poor outcome when its effect was adjusted for the rest of the variables. Conclusions: This study showed that antimicrobial therapy was not associated with a poor outcome in non-bacteraemic patients with positive blood cultures drawn through a CVC.